Effect of Insecticide Dichlorvos on Ovaries of Mosquito Fish Gambusia affinis (Baird and Girard) (Baghdad Science Journal, 2011)
The toxicity of insecticide dichlorvos (90%) was tested in ovaries of mosquito fish using three sublethal concentrations (0.3, 0.6, 0.8 µg/L) and studied their effects on the means of body and ovary weights, gonadosomatic index, ovum size and ova number. Results showed that there was a significant (P